Response of tomato plant to different rates of zinc nanoparticles spraying as foliar fertilization . - El-Raie, A.; Abd El-Rahman, A. A.; Hassan, H. E.; Arafat, A. A. (2015)
A field expeiment was carried out on a clayey soil in egypt cultivated with tomato plants (Lycopersion esculentim mill) . and furrow irrigation with nile water , to study the potential benefits of iron nutrient in nanoparticals form (fenps) vis .
Includes reference
Summary in Arabic
Keywords: Foliar feeding; tomato -- Fertilizers; Zinc fertilizers